The Roman imperialist practice in Saguntum: debates andreinterpretations on the annexation process - Campos, Carlos Eduardo da Costa (Romanitas - Revista de Estudos Grecolatinos, 2025)
The process of Roman territorial annexation, as observed in the case of Sagunto, is a clear example of Roman imperialist practices. Sagunto, part of Hispania Citerior and, later, Hispania Tarraconensis, illustrates how Rome implemented its control through urban reconstruction and the co-option of local elites. The city, devastated by Carthage during the Second Punic War, was rebuilt by the Romans, who used strategies such as administrative installation and the creation of municipalities to integrate the population into the Roman power system. Annexation was not a homogeneous process, varying according to Rome’s political, economic, and strategic needs. This process also reflected the complexity and variability of the relationships between Rome and the subjugated societies, highlighting the importance of considering historical and cultural specificity in the analysis of Roman imperialism.